2017
DOI: 10.1039/c7gc01519d
|View full text |Cite
|
Sign up to set email alerts
|

Tropylium salts as efficient organic Lewis acid catalysts for acetalization and transacetalization reactions in batch and flow

Abstract: Tropylium salts were reported as organic-Lewis acids to efficiently catalyze acetalization reactions in batch and flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…It fulfils Hückel's rule of aromaticity and enjoys an interesting balance of stability and reactivity . The Lambert group and our group have recently demonstrated the versatile chemistry of tropylium ion where this carbocation can act as a Lewis acid, an electrophile or an oxidant . Herein, we exploit these chemical reactivities to develop a convenient and practical protocol (Scheme ) to access a family of tropylium organic dyes with strong absorption in the visible range.…”
Section: Methodsmentioning
confidence: 99%
“…It fulfils Hückel's rule of aromaticity and enjoys an interesting balance of stability and reactivity . The Lambert group and our group have recently demonstrated the versatile chemistry of tropylium ion where this carbocation can act as a Lewis acid, an electrophile or an oxidant . Herein, we exploit these chemical reactivities to develop a convenient and practical protocol (Scheme ) to access a family of tropylium organic dyes with strong absorption in the visible range.…”
Section: Methodsmentioning
confidence: 99%
“…In 2003, Ma et al presented an efficient and chemoselective method for the preparation of diethyl acetals in good to excellent yields (63-96%) via the acetalization 178,[396][397][398][399][400][401][402][403][404][405][406][407][408] of aldehydes/ ketones with TEOF using TiO 2 /SO 4 2À in reuxing ethanol for 25 min to 3 h. It was found that, in competitive reactions, aldehydes and cyclic aliphatic ketones revealed excellent chemoselectivity. 408 The reaction of enamines (470) with trialkyl orthoformates (4,5) was also accomplished in the presence of BF 3 $OEt 2 in CH 2 Cl 2 to give a-dialkoxymethyl carbonyl compounds (471), aer hydrolysis, in 61-85% yields within 1 h (Scheme 138).…”
Section: Acetalization Reactionmentioning
confidence: 99%
“…Various papers are published by discussing the role of individual salts, their selective way of transformation, role in asymmetric synthesis and many more. Some of the recent influencing research on application of salts in organic synthesis are use of diaryliodonium salts for novel arylation [20], applications of ferrocenium salts [21], salt as linker source [22], pyridinium salts as radical reservoir [23], use of vinyliodonium salts for alkenylation of nitriles [24], use of sulfonium salts for synthesis of spirocyclopropanyl paradienones [25], use of phosphonium salts for selective functionalization of pyridines [26], tropylium salts as lewis acid to catalyze acetalization and transacetalization [27], use of Phenyltrimethylammonium salts in nickel-catalyzed methylation of C− H bonds [28], aryldiazonium salts for carbohydroxylation of styrenes [29], synthesis of bicyclic aziridines from pyridinium salts [30], nucleophilic arylation with tetraarylphosphonium salts [31], application of trimethylsilanolate alkali salts in organic synthesis [32], use of α, β-unsaturated acylammonium salts for asymmetric organocatalysis [33], review on cesium salts use in organic synthesis [34], iodonium salts as benzyne precursors [35], use of bunte salts as a sulfur source for synthesis of 3-thioindoles [36], and C− H functionalization of arenes by diaryliodonium salts [37] etc.…”
Section: Diversified Use Of Salts In Organic Synthesismentioning
confidence: 99%